2022
DOI: 10.3389/fcell.2022.1092776
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and long non-coding RNAs in cartilage homeostasis and osteoarthritis

Abstract: During the last decade, osteoarthritis (OA) has become one of the most prevalent musculoskeletal diseases worldwide. OA is characterized by progressive loss of articular cartilage, abnormal remodeling of subchondral bone, hyperplasia of synovial cells, and growth of osteophytes, which lead to chronic pain and disability. The pathological mechanisms underlying OA initiation and progression are still poorly understood. Non-coding RNAs (ncRNAs) constitute a large portion of the transcriptome that do not encode pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…However, in addition to imaging modalities and tools for osteosarcopenia diagnosis, the biochemical assessment of bone and muscle metabolism has been also proposed to improve early diagnosis and screening. Furthermore, in recent years, the scientific community has focused its attention on a novel class of potential diagnostic biomarkers, both for osteoporosis and sarcopenia, named circulating cell-free miRs [ 15 , 16 , 17 , 18 , 19 , 20 ]. Several studies have shown that miRs in cultured cells or animal models may play pivotal roles in osteoporosis and sarcopenia, but fewer data are available on circulating miRs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in addition to imaging modalities and tools for osteosarcopenia diagnosis, the biochemical assessment of bone and muscle metabolism has been also proposed to improve early diagnosis and screening. Furthermore, in recent years, the scientific community has focused its attention on a novel class of potential diagnostic biomarkers, both for osteoporosis and sarcopenia, named circulating cell-free miRs [ 15 , 16 , 17 , 18 , 19 , 20 ]. Several studies have shown that miRs in cultured cells or animal models may play pivotal roles in osteoporosis and sarcopenia, but fewer data are available on circulating miRs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in recent years, the scientific community has focused its attention on a novel class of potential diagnostic biomarkers, both for osteoporosis and sarcopenia, named circulating cell-free miRs [ 15 , 16 , 17 , 18 , 19 , 20 ]. Several studies have shown that miRs in cultured cells or animal models may play pivotal roles in osteoporosis and sarcopenia, but fewer data are available on circulating miRs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Thus, given the increasing prevalence of osteosarcopenia in elderly populations, we systematically evaluated the potential clinical biomarker utility of circulating miRs in patients with a diagnosis of osteoporosis and sarcopenia versus healthy controls and evaluated the shared miRs between these two pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding RNAs (ncRNAs) are taking on an emerging role in many orthopedic diseases [ 18 , 19 , 20 , 21 ], and among these also in scoliosis. In fact, a number of studies have shown there was a dysregulation of miRNAs in scoliosis and have linked this to the pathogenesis of the disease [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The miRNAs play an important role in the skeletal system including cartilage and bone development by regulating key processes, such as chondrocyte proliferation, differentiation and apoptosis [ 14 ]. Chondrocyte-specific deletion of DICER in the growth plate of mice reduced the number of proliferating chondrocytes, increased hypertrophic chondrocytes and led to severe skeletal defects and premature death [ 15 ].…”
Section: Introductionmentioning
confidence: 99%